THE IMPACT OF AGE-FRIENDLY ENVIRONMENTS ON THE WELLBEING OF OLDER ADULTS: EMPIRICAL EVIDENCE FROM SARAWAK - Jeffery, Stephen; Nur Azimah, Azman; Md Mizanur, Rahman; Rosalia, Saimon; Gui, Hun Chuen (2025)
Ageing significantly affects the psychosocial well-being of older adults, with growing evidence emphasizing the influence of environmental factors on their psychological and social health. Sarawak, which has the second-highest proportion of older adults in Malaysia, has not previously been studied in relation to the connection between age-friendly environments (AFEs) and psychosocial well-being. This study aimed to examine the association between AFEs and the psychosocial well-being of older adults in Sarawak. A cross-sectional study was conducted involving 1,077 respondents aged 60 years and above. AFEs were evaluated using a perception-based measure covering eight domains: housing, social participation, respect and social inclusion, civic participation and employment, communication and information, community support and health services, outdoor spaces and buildings, and transportation. Psychosocial well-being was assessed across social and psychological domains. Robust regression analysis was used to determine the associations between AFE indicators and psychosocial well-being indicators. The findings revealed positive relationships between most AFE indicators and psychosocial well-being, suggesting that favorable perceptions of age-friendly environments correspond with improved psychosocial outcomes among older adults. Of the eight domains analyzed, six were statistically significant predictors of psychosocial well-being: housing (estimate = 0.54, SE = 0.07, 95% CI = 0.40, 0.67), social participation (estimate = 0.14, SE = 0.05, 95% CI = 0.05, 0.24), respect and social inclusion (estimate = 0.22, SE = 0.06, 95% CI = 0.10, 0.34), civic participation and employment (estimate = 0.69, SE = 0.08, 95% CI = 0.55, 0.85), communication and information (estimate = -0.19, SE = 0.06, 95% CI = -0.31, -0.07), and transportation (estimate = 0.17, SE = 0.03, 95% CI = 0.11, 0.24). Conversely, community support and health services (estimate = -0.03, SE = 0.04, 95% CI = -0.10, 0.05) and outdoor spaces and buildings (estimate = -0.01, SE = 0.04, 95% CI = 0.11, 0.24) were not significant predictors. This study provides empirical evidence linking the domains of AFEs to the psychosocial well-being of older adults in Sarawak. The results highlight the critical importance of age-friendly environmental factors in fostering better wellbeing among the ageing population. Understanding these associations is crucial for designing policies and interventions that promote supportive environments for older adults.